Anacharsis in der Diskussion über das Kriterion der Wahrheit in Sextus Empiricus' Adversus Mathematicos: Versuch einer Erläuterung mit Hilfe verschiedener Tools zur Visualisierung von Kookkurrenzen (eAQUA/eXChange TagPies) - Friedrich Meins (Digital Classics Online)
The paper argues that the (obviously fictional) quote attributed to the legendary Scythian sage Anacharsis in the work of the sceptic Sextus Empircus is more likely to be understood as some kind of ironical twist than as a substantial hint towards a specific philosophical background: At the time of Sextus, Anacharsis was best known as the proverbial wise man. As such, he denies the existence of a criterion of truth that is discussed in the respective passages. At the same time, the figure of the wise man itself is seen as a criterion of truth by several dogmatic philosophers Sextus is arguing against. This leads to a paradoxical situation in which the criterion denies the existence of the criterion explicitly, and, on a more structural level, even the wise man per se the existence of wise men in general.